Erosion and accretion in the Ria de Aveiro inlet (N Portugal) and exportation of fine–grained sediments to the shelf - Martins, V.; Grangeia, C.; Jesus, C. C.; Martins, P.; Laut, L. M.; Sequeira, C.; Dias, J.M.; Silva, P. A.; Abrantes, I.; Ferreira da Silva, E.; Rocha, F. (Journal of Iberian Geology, 2011)
Harbours are important man made economic structures that are usually constructed in hydrodynamic complex settings. Their life/ service cycle, integrity and maintenance are highly dependent on the knowledge of these settings and the capability to predict future changes and thus their economic impact. In this paper, data regarding bottom and suspended sediments of the Aveiro Harbour inlet were gathered and analysed. Measurements of suspended sediment concentrations (SSC) in the Aveiro inlet were taken during eight tidal cycles in 2007, including spring and neap tides throughout winter and summer oceanographic regimes. Results suggest significant temporal variability. Sediments were imported from the ocean sink, mostly near the south jetty and the western side of the Mira Channel, as textural, mineralogical, compositional, geochemical and microfaunal data of bottom sediments suggest. Higher stabilization of the Aveiro Harbour structures is achieved on these accretional areas. The high tidal-current velocities contribute to the erosive character which dominates the central area of the entrance channel, which is located between both breakwaters and close to the north jetty; thus some segments of the north jetty could become damaged through erosion. This is evidenced as much bottom sediments characteristics as patterns of SSC. SSC are in general higher during the winter, due to climatic conditions, current velocities, wind stress and greater availability of sediments provided by the local-river flooding. Our data also suggest that SSC are predominantly higher during ebb and low tide throughout the year, as compared to periods of flood, when a higher flux of sediments is transported seaward than landward. The lagoon exports to the continental shelf mostly muddy sediments, composed essentially of quartz and phyllosilicates.